Kidney Function and Cognitive Impairment in People Aged 80 Years and Over with Untreated Hypertension: A Cross-Sectional Survey - Han Wang; Tao Liu; Ying-ying Cai; Hui Jiang; Han-xiong Liu; Cai Lin (Karger Publishers, 2016)
Background/Aims: Both kidney dysfunction and cognitive impairment are common problems in hypertensive patients. However, few studies have explored the association between these conditions in hypertensive patients aged 80 or over. The current study was undertaken to determine the impact of chronic kidney disease (CKD) and estimated glomerular filtration rate (eGFR) on cognitive impairment among an 80-year-old population with untreated hypertension in China. Methods: A total of 395 hypertensive patients aged 80 or over were assessed for the presence of cognitive impairment according to the 30-item Mini-Mental State Examination (MMSE). Cognitive impairment was defined as a score below 24 on MMSE. eGFR was evaluated using the Chinese Modification of Diet in Renal Disease equation. CKD was defined according to categorical approach, which is based on "YES" (eGFR below 60 ml/min) or "NO" (eGFR above 60 ml/min). Results: The mean (SD) age was 83.0 ± 2.6 years for the sample, of whom 69.8% were female. There were 59 (14.9%) and 280 (71.1%) prevalent cases of CKD and cognitive impairment, respectively. CKD patients were older, had higher scores on Activity of Daily Living (ADL), and lower score on MMSE. After controlling for potential confounding, multiple logistic regressions demonstrated that both CKD and eGFR were associated with cognitive impairment in hypertensive patients aged 80 or over. Conclusion: Our study found that both CKD and eGFR were associated with cognitive impairment among hypertensive patients aged 80 or over in China. Therefore, targeted screening for cognitive impairment should be considered in these patients with CKD.